Minat Publik Terhadap Investasi P2P Lending Fintech Syariah di Alami Sharia: Produk, Akad, Imbal Hasil, Tingkat Keberhasilan Bayar - Orryza Sativa Devi; Destian Arshad Darulmalshah Tamara; Muhamad Umar Mai (Indonesian Journal of Economics and Management, 2022)
This research aims to determine the level of public interest on P2P lending investment through sharia fintech. The independent variables used are product, agreement, yield, and levels of return success which will be analyzed for their effect on the dependent variable, namely public interest on Islamic P2P lending investment. This research used a path analysis method. The data used in this research are primary data obtained directly through the results of questionnaires distributed to respondents followers of the official ALAMI Sharia Instagram social media account. The results showed that the Product variable has a direct and significant effect on the Interest in Investing in Sharia P2P Lending. Sharia Agreement variable has a direct but insignificant effect on the Interest in Investing in Sharia P2P Lending. Percentage of Yield variable has a direct but insignificant effect on the Interest in Investing in Sharia P2P Lending. Levels of Return Success variable has a direct and significant effect on the Interest in Investing in Sharia P2P Lending.